2013
DOI: 10.1188/13.cjon.654-658
|View full text |Cite
|
Sign up to set email alerts
|

The Benefits of Medical Qigong in Patients With Cancer: A Descriptive Pilot Study

Abstract: Medical Qigong (MQ) is a mind-body exercise that includes movement and meditation and is beneficial in reducing high blood pressure, high cholesterol, anxiety, stress, pain, and incidence of falls. The purpose of the current study was to determine whether patients with cancer and survivors who participated in an MQ class experienced a change in fatigue, depression, and sleep from a preintervention evaluation to a postintervention evaluation. Participants were patients diagnosed with cancer who participated in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 41 publications
(32 reference statements)
0
5
0
Order By: Relevance
“…QE, which is widely applied in complementary and alternative medicine, can increase blood circulation, improve lung and heart function, regulate homeostasis, moderate emotions, and allow self-healing. 20 - 22 …”
Section: Introductionmentioning
confidence: 99%
“…QE, which is widely applied in complementary and alternative medicine, can increase blood circulation, improve lung and heart function, regulate homeostasis, moderate emotions, and allow self-healing. 20 - 22 …”
Section: Introductionmentioning
confidence: 99%
“…However, they were motivated to attend sessions and even conducted additional home practice due to the ease of the Qigong style, as well as the effects of increased inner calm and improved sleep experienced, especially from the La Qi and Rou Fu methods which emphasize on meditation and relaxation. Considering that stress is one of the main causes [75][76][77] and aggravators of insomnia 4 in cancer patients and that previous studies have noted improvements in stress levels with mind-body exercises such as yoga 74 and Qigong, 78,79 though not objectively evaluated in this study, the stress reduction reported by participants may have contributed to the sleep improvements. Further studies are warranted to investigate the relationship between Qigong, the perception of stress and one's state of wellbeing.…”
Section: Discussionmentioning
confidence: 80%
“…According to the holistic concept of Chinese Medicine, human must live in harmony with nature to achieve total health. 55 Zhineng Qigong is different from other forms of Qigong studied for insomnia in cancer patients, as the practice of Zhineng Qigong integrates the Qi of nature and the Qi of human 12,24 to synchronize the human body system with nature including the human circadian rhythm that affects sleep. 53,[56][57][58] Therefore, this study aimed to investigate the feasibility and potential effects of a 3-week Zhineng Qigong intervention for insomnia in cancer patients.…”
mentioning
confidence: 99%
See 2 more Smart Citations